Implementasi Etika Literasi Digital Bagi Siswa Man 2 Deli Serdang - Chairuna, Sasmita; Asari, Hasan (Jayapangus Press, 2025)
MAN 2 Deli Serdang organizes a smart digital class and forms a special extracurricular called AEJ (Aliyah Education's Journalist) as an effort to improve digital literacy among students. This study aims to answer problems related to policies, implementation, and evaluation of digital literacy ethics in increasing awareness of MAN 2 Deli Serdang students about the importance of using digital technology properly. This type of research is qualitative field research, using qualitative descriptive methods in analyzing data. This study found that policies related to digital literacy ethics for MAN 2 Deli Serdang students are in line with the policy of implementing smart digital classes (SDC) or digital classes and AEJ (Aliyah Education's Journalist). The implementation of digital literacy ethics for MAN 2 Deli Serdang students is by providing guidance on the proper use of digital media in digital classes and the ethics of creating digital works. Evaluation of digital literacy ethics for MAN 2 Deli Serdang students is carried out routinely at the end of each month. Teachers who teach in digital classes and AEJ mentors said that MAN 2 Deli Serdang students already understand the ethics of using digital media properly and responsibly.